Corn Cob Compost An Environmentally Friendly Base Fertilizer Solution PT Nuansa Cipta Indowarna Mandiri - Dipa Aditya (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
This demonstration plot study of the use of corn cake compost as a base fertilizer for corn farming on rain-fed land owned by PT. Nuansa Cipta Indowana Mandiri on Jl. Lumbang km. 07, Sumberkramat Village, Tongas District, Probolinggo Regency aims to analyze the socio-economic impacts of utilizing the company's abandoned/idle rain-fed land. This idle land utilization is intended to increase farm income and contribute to national harvest yields as a basis for food security. It also aims to determine the economic value of corn cake industrial waste as compost that can improve soil fertility. The data used are secondary data in the form of Corn Cake Flour Analysis results and primary data sourced from the demonstration plot data on the use of Corn Cake Flour compost as a base fertilizer for corn planting in rain-fed rice fields owned by PT. Nuansa Cipta Indowarna Mandiri in Sumber Kramat Village, Tongas District, Probolinggo Regency.The method used in this study was purposive sampling with observation, interviews, and documentation. Data were collected/processed and then analyzed using quantitative descriptive methods. The results of the study indicate that the abandoned/idle land of PT Nuansa Cipta Indowarna Mandiri is rain-fed land that has been planted with rice twice since 2009, namely in 2014 and in 2025 in a demonstration plot using corn filter cake compost, the land was planted with corn. Planting corn on a 3,000 m² plot produced 1,400 kg of dry corn kernels, with a total cost of IDR 6,713,000, - generating income of IDR 1,267,000, - the harvest yield decreased because 20% of the corn seedlings died due to heavy rain for 4 days. The R/C ratio of 1.19 is greater than 1, which means it is economically feasible. Socially, corn farming on the idle/abandoned land can absorb labor, provide cattle feed in the form of corn stalks for farm laborers harvesting, and contribute to corn harvest yields that can increase the number of corn harvests nationally. Corn Flour which is sugar waste from corn as the basic ingredient can be used as organic fertilizer because it has an organic C content of 25.56% (SNI Solid Organic Fertilizer Organic C content >15%) and a very low Fe content, namely available Fe 83.3 and total Fe 366 (SNI maximum available Fe 500 and maximum total Fe 15,000).Key words: Rainfed lowland farmers, income contribution, side job.